Effects of fuel injection parameters on premixed charge compression ignition combustion and emission characteristics in a medium-duty compression ignition diesel engine. (February 2021) - Molina, Santiago; García, Antonio; Monsalve-Serrano, Javier; Villalta, David
From the different power plants, the compression ignition diesel engines are considered the best alternative to be used in the transport sector due to its high efficiency. However, the current emission standards impose drastic reductions for the main pollutants, that is, NO x and soot, emitted by this type of engines. To accomplish with these restrictions, alternative combustion concepts as the premixed charge compression ignition are being investigated nowadays. The objective of this work is to evaluate the impact of different fuel injection strategies on the combustion performance and engine-out emissions of the premixed charge compression ignition combustion regime. For that, experimental measurements were carried out in a single-cylinder medium-duty compression ignition diesel engine at low-load operation. Different engine parameters as the injection pattern timing, main injection timing and main injection fuel quantity were sweep. The best injection strategy was determined by means of a methodology based on the evaluation of a merit function. The results suggest that the best injection strategy for the low-load premixed charge compression ignition operating condition investigated implies using a high injection pressure and a triple-injection event with a delayed main injection with almost 15% of the total fuel mass injected.